2018
DOI: 10.1002/polb.24610
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic postpolymerization of 3D‐printed photopolymer nanocomposites: Effect of cellulose nanocrystal and postcure temperature

Abstract: Cellulose nanocrystal (CNC) reinforced methacrylate (MA) resin nanocomposite was prepared by 3D stereolithography printing. A postcure process, where the printed nanocomposite was heat-treated under different temperatures, was applied to improve the property of the printed nanocomposites. To investigate the effect of CNC and postcure temperature on the kinetic behavior of the postpolymerization of printed nanocomposites, Fourier-transform infrared spectroscopy and differential scanning calorimetry measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…It has been reported that the unreacted resin in the printed sample will polymerize when the temperature increases, releasing heat in the processing. 28 As shown in Table 2, all of the non-post-cured samples have exothermic enthalpy, suggesting the presence of unreacted resin in the printed samples. The increased concentration of lignin leads to higher exotherm enthalpy values, which implied that increased amounts of unreacted resin was present in the composites.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that the unreacted resin in the printed sample will polymerize when the temperature increases, releasing heat in the processing. 28 As shown in Table 2, all of the non-post-cured samples have exothermic enthalpy, suggesting the presence of unreacted resin in the printed samples. The increased concentration of lignin leads to higher exotherm enthalpy values, which implied that increased amounts of unreacted resin was present in the composites.…”
Section: Resultsmentioning
confidence: 95%
“…The −OH stretching was attributed to the adsorption of water and −OH from lignin during the fabrication process, as previously reported. 3,25,28 Due to the low contents of lignin, all of the abovementioned peaks of the printed control sample did not show significant changes of intensities in the spectra compared with the composites incorporated with a different amount of lignin from 0.2 to 1.0 wt %. However, a subtle difference between the printed control sample and the composites was found with respect to the peaks located at 1638 and 1400–1100 cm –1 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The realization of these advantages depends on the stability and efficiency of the photocurable resin materials. Generally, the common resins for stereolithography are polyurethane, epoxy, and acrylate and so on . Among these liquid resins, acrylate has gained the most attention due to its relatively high transparency and accuracy as well as low cost, making it more compatible for stereolithography, especially in model display area, such as teaching model display, dental model, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The curing rate of photosensitive resin is about 65–90 percent along with the incorporation of epoxy [ 23 ]. In order to complete the reaction, heat, ultrasonic energy, and UV light can be used in post processing [ 24 , 25 ]. The mechanical properties such as tensile strength and hardness can be effectively improved to a certain extent after post-curing treatment.…”
Section: Introductionmentioning
confidence: 99%